2009
DOI: 10.1016/j.vetmic.2009.01.016
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the volatile metabolites found in mastitis milk

Abstract: The origin of the volatile metabolites found in mastitis milk. Veterinary Microbiology, Elsevier, 2009, 137 (3-4) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…On the other hand, excessive sesquiterpenoids can lead to toxic effects, such as producing spastic neurotoxins and pro-in ammatory factors [51]. Hettinga et al [52] found that the toxic volatile metabolites, dimethyl sul de, in milk from mastitis cows mainly originated from pathogens, such as Staphylococcus aureus, Streptococcus uberis and E.coli. It is speculated that the increase of 10beta-Hydroxy-6beta-isobutyrylfuranoeremophilane in the rumen may be a result of the increased rumen pathogens or the damage of blood-milk barrier.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, excessive sesquiterpenoids can lead to toxic effects, such as producing spastic neurotoxins and pro-in ammatory factors [51]. Hettinga et al [52] found that the toxic volatile metabolites, dimethyl sul de, in milk from mastitis cows mainly originated from pathogens, such as Staphylococcus aureus, Streptococcus uberis and E.coli. It is speculated that the increase of 10beta-Hydroxy-6beta-isobutyrylfuranoeremophilane in the rumen may be a result of the increased rumen pathogens or the damage of blood-milk barrier.…”
Section: Discussionmentioning
confidence: 99%
“…For example, specific volatile metabolites detected in mastitis milk samples are formed by and are specific to each pathogen (Hettinga et al 2009). Other components are more or less affected depending on the pathogen.…”
Section: Changes In Milk Associated With a Rise In The Scc And Variatmentioning
confidence: 99%
“…This requires an increase in endothelial permeability, which induces not only the transfer of PMN from blood to milk but also other blood components such as bovine serum albumin (BSA). Lipolysis in milk can be explained by the disturbance of the milk-blood barrier which allows the transfer of esterases from blood to mastitic milk (Hettinga et al 2009). Another example of increased permeability is found in transferrin (an iron transporter), which is not produced in the mammary gland of ruminant (Sanchez et al 1992) but comes from blood serum (OllivierBousquet 1998) and rapidly increases in E. coli mastitis .…”
Section: Increased Endothelial Permeabilitymentioning
confidence: 99%
“…However, little information exists about the changes this may induce in the biochemical composition of human milk. In contrast, it is well known that, in bovine mastitis, the metabolism of the infecting bacteria changes the volatile compound profile [14]. …”
Section: Introductionmentioning
confidence: 99%